Research Trends in Ethnoscience in Science Education: A Bibliometric Analysis Based on the Scopus Database - Parham Saadi; Misbah Misbah; Qamariah Qamariah; Noor Izzati Pratiwi; Surya Haryandi; Muhdi Harto; Ahmad Syarkowi (Gawi: Journal of Action Research, 2026)
This study aims to analyze the development of ethnoscience research in science learning using publications indexed in Scopus. The study used a descriptive bibliometric approach to documents on ethnoscience and science learning published between 1998 and 2026. The analysis focused on publication growth trends, the most productive affiliations and countries, primary publication sources, the most influential authors, and a keyword co-occurrence map using VOSviewer. The analysis shows that ethnoscience research in science learning experiences has fluctuated but has been increasing, with the largest spike in 2025. Publication productivity is dominated by Indonesia at both the country and institutional levels, with Indonesian universities occupying the top position as the most productive affiliates. At the source level, publications are concentrated in journals oriented towards science education and contextual learning innovation. Citation analysis shows that scientific influence remains concentrated in a small number of authors, while the keyword map indicates that ethnoscience is a key node connected to the themes of science education, project-based learning, scientific literacy, critical thinking skills, indigenous science, and context-based learning. These findings confirm that ethnoscience has evolved from simply integrating local knowledge into learning to a multidimensional, contextual, and relevant pedagogical approach aimed at strengthening 21st-century competencies. This research has implications for the importance of expanding international collaboration, strengthening publication quality, and developing more innovative and impactful ethnoscience-based science learning models